Private Higher Education in Post-Communist Europe
XIII, 329 p.
Keywords: An exploration of international privatization of higher education in post-communist Europe from two top scholars in the field. Levy and Slantcheva trace the ramifications of globalization in Central and Eastern Europe as well as in the former Soviet republics.